FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ASMA BRONKIAL PADA ANAK DI WILAYAH KERJA PUKESMAS AMBUNTEN - tiyah, khomariyatul kip; Mulyadi, Eko; Eka Puspitasari, Dian; Hannan, Mujib (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2024)
Asthma is the most common chronic respiratory disease found in children or adults, characterized by shortness of breath, wheezing, coughing, and impaired expiratory flow. This study aims to determine the factors associated with the incidence of Bronchial Asthma in children in the Ambunten Health Center Work Area. The type of research used in this study is quantitative, the research design used in this study is correlation with case control design. The type of sampling used is Non Probability Sampling which was carried out in the Ambunten Health Center Work Area on May 17-31, 2024. The results of the study showed that P. Value: 0.00 = ≤ 0.05 = there is a relationship between cigarette smoke and Asthma. Oddratio: 21.5 = people exposed to cigarette smoke are 21.5 times more likely to get Asthma than people who do not have Asthma, P. Value: 0.02 = ≤ 0.05 = there is a relationship between weather changes and Asthma. Odratio: 7.8 = people exposed to weather changes are 7.8 times more likely to get Asthma than people who do not have Asthma, P. Value: 0.015 = ≤ 0.05 = there is a relationship between stress and Asthma. Odratio: 0.214 = people exposed to stress are 0.214 times more likely to get Asthma than people who do not have Asthma. The conclusion obtained is that most children suffering from Bronchial Asthma in the Ambunten Health Center Work Area are exposed to cigarette smoke, weather changes, and experience high levels of stress.